The effect of teacher self-efficacy, teacher resilience, and emotion regulation on teacher burnout: a mediation model - Li, Shanshan (Frontiers in Psychology, 2023)
This research was set to examine the interconnections among teacher self-efficacy and teacher resilience, emotion regulation, and teacher burnout among Chinese English as a foreign language (EFL) teachers. A sample of 638 Chinese EFL teachers completed self-report measures of teacher self-efficacy and teacher resilience, emotion regulation, and teacher burnout. Confirmatory factor analysis was used to confirm the construct validity of the measures, and structural equation modeling was employed to test the structural model. The results showed that teacher self-efficacy and resilience negatively and directly predicted teacher burnout. Furthermore, teacher emotion regulation was found to have an indirect effect on teacher burnout through the mediation of teacher resilience, supporting that the partial mediation model was found to be the best fitting model. These findings have important implications EFL teaching programs.